Legaculturation: Turning Laws into a Culture - Ghaleb, Belal Dahiam Saif (PT. Riset Press International, 2024)
The interaction between law and culture is fundamental to the functioning of any society. While laws are formal rules enforced by state institutions, culture encompasses the shared values, beliefs, and practices of a society. In order to eliminate problems such as the conflict between law and culture, the pressure of law on culture, the society's behavior against the law, and similar problems, law must be adapted to the culture and existing laws must be made a culture of the society. This article explores the process of transforming legal norms into cultural ones, emphasizing the mechanisms through which laws are internalized and become an integral part of social behavior. By examining historical precedents, theoretical frameworks, and contemporary examples, the article demonstrates how legal norms can shape and be shaped by cultural norms, transcending their formal boundaries. More significantly, it illustrates how the state's promulgation, enforcement, and potential future enactment of laws can be rendered more palatable, acceptable, and culturally integrated to both the state and society. The article posits that as society embraces laws as part of its culture, not only will the state's expenditure on ensuring security decrease, but societal trust will also increase, reducing conflicts and insecurities in the application of laws. The article also, introduces the concept of Legaculturation and emphasizes the importance of turning (transforming) laws into a culture. This comprehensive research provides a professional and detailed examination of the concept of Legaculturation by combining information from existing literature. Ultimately, the article assumes that society will thrive in welfare underpinned by a harmonious blend of legal and cultural norms.